Carbohydrate-binding domain CBM63 of microbial expansin-like BsEXLX1 facilitates the adsorption of expansin-related proteins to hemicelluloses in plant secondary cell walls - Pramod Sivan; Deepika Dahiya; Ylenia Jabalera; Taru Koitto; Raul Perez-Jimenez; Ewa J. Mellerowicz; Emma Master; Francisco Vilaplana (Biotechnology for Biofuels and Bioproducts)
Abstract Background Overcoming lignocellulose recalcitrance to enzymatic or chemical processing is a prerequisite for biorefinery applications. Expansins and loosenins are non-lytic proteins that could assist reducing this recalcitrance by disrupting the intermolecular contacts between plant cell wall components. Here, immunolocalization with fluorescence and transmission electron microscopy (TEM) were used to study the ability of a Bacillus subtilis expansin-like protein (BsEXLX1), a Phanerochaete carnosa loosenin protein (PcaLOOL12) and a fusion protein of PcaLOOL12 with the carbohydrate-binding module 63 (CBM63) of BsEXLX1 (i.e., PcaLOOL12-CBM63) to bind secondary cell walls (SCW) of aspen fibres, including fresh aspen wood, milled wood fibres (MWF) and MWF subjected to subcritical water extraction. Results The immunofluorescence labelling of fresh wood samples showed a weak signal for PcaLOOL12 and a strong signal for BsEXLX1 and PcaLOOL12-CBM63, suggesting the importance of CBM63 for protein adsorption to SCW components. TEM analysis after immunogold labelling revealed the presence of BsEXLX1 and PcaLOOL12-CBM63 in all secondary cell wall layers. Pretreatment of wood samples with the proteins reduced the binding of glucomannan- and glucuronoxylan-specific monoclonal antibodies. Similarly, protein adsorption to MWF was higher before subcritical water extraction. Together, these results suggest the adsorption of BsEXLX1 and PcaLOOL12-CBM63 to SCWs was mediated at least in part by their interaction with hemicelluloses. Conclusions Our study demonstrates that microbial expansin-related proteins can bind to the secondary walls of aspen wood through potential interaction of CBM63 with hemicelluloses.